Applied Authentic Assessment in Engineering Technology Courses for Academic Integrity - Butterworth, Carina (Canadian Perspectives on Academic Integrity, 2021)
Teamwork and individual work within the classroom and in the online environment have seen a shift in how students engage in course materials and in how the material has been delivered to the students. Individualizing projects has become a way to both engage the student and to harness their strengths which results in improved adherence to academic integrity policies. This presentation will discuss my experience in developing, implementing and creating authentic assessments in my classroom to promote healthy academic integrity activities in the engineering technology discipline; and ending with my reflections and recommendations of the process. The take home objective for attendees is to adapt new ideas for authentic assessment and develop a process for implementing these assessments within their own classrooms. It may also appeal to policy creators to see the different ways instructors are adapting their materials for education and engagement, rather than punitive actions.